SARS‐CoV‐2 infection activates CREB/CBP in cellular cyclic AMP‐dependent pathways. Issue 1 (21st December 2022) - Yang, Qi; Tang, Jielin; Cao, Juan; Liu, Fengjiang; Fu, Muqing; Xue, Bao; Zhou, Anqi; Chen, Sijie; Liu, Junjun; Zhou, Yuan; Shi, Yongxia; Peng, Wei; et al.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has caused a global coronavirus disease 2019 (COVID‐19) pandemic that has affected the lives of billions of individuals. However, the host‐virus interactions still need further investigation to reveal the underling mechanism of SARS‐CoV‐2 pathogenesis. Here, transcriptomics analysis of SARS‐CoV‐2 infection highlighted possible correlation between host‐associated signaling pathway and virus. In detail, cAMP‐protein kinase (PKA) pathway has an essential role in SARS‐CoV‐2 infection, followed by the interaction between cyclic AMP response element binding protein (CREB) and CREB‐binding protein (CBP) could be induced and leading to the enhancement of CREB/CBP transcriptional activity. The replication of Delta and Omicron BA.5 were inhibited by about 49.4% and 44.7% after knockdown of CREB and CBP with small interfering RNAs, respectively. Furthermore, a small organic molecule naphthol AS‐E (nAS‐E), which targets on the interaction between CREB and CBP, potently inhibited SARS‐CoV‐2 wild‐type (WT) infection with comparable the half‐maximal effective concentration (EC50 ) 1.04 μM to Remdesivir 0.57 μM. Compared with WT virus, EC50 in Calu‐3 cells against Delta, Omicron BA.2, and Omicron BA.5 were, on average, 1.5‐fold, 1.1‐fold, and 1.5‐fold higher, respectively, nAS‐E had a satisfied antiviral effect against Omicron variants. Taken together, our study demonstrated the importance of CREB/CBP induced by cAMP‐PKA pathway during SARS‐CoV‐2 infection, and further provided a novel CREB/CBP interaction therapeutic drug targets for COVID‐19.